Heavy metal footprints in landfill-proximate soils of Jashore, Bangladesh: An index-based risk assessment - Sanjida Sultana Santa; Md Kamal Hossain; Kowshik Das Karmaker; Mohammad Moniruzzaman; Md. Harunor Rashid Khan (PLoS ONE, 2026)
Disposal of the household originated and industrial hazardous materials with municipal solid waste (MSW) into the open dumping sites is the usual practice in Bangladesh which raises concerns regarding the pollution of the regions adjacent to these landfill sites. The study evaluated the impact of landfill techniques and environmental factors on soil contamination by potentially toxic elements and the corresponding environmental hazards. This study assessed the potential ecological hazards linked to a landfill s ite in southwestern Bangladesh. ICPMS and AAS were used to detect eleven heavy metals in soils from the landfill. This analysis aimed to uncover the origin, degree of contamination, geographical representation, and the environmental and human health hazards connected with these metals. Mean levels of the metals in mg/kg were As (12.02 ± 4.40); Hg (0.611 ± 0.441); Cd (0.606 ± 0.487); Pb (37.5 ± 14.08); Cr (46.9 ± 10.06); Zn (260.7 ± 201.0); Co (16.03 ± 3.02); Ni (39.5 ± 11.6); Cu (260.7 ± 55.79); Mn (613.2 ± 189.6); Fe (26087 ± 4396). This investigation discovered significant amounts of As, Hg, Cd, Pb, Zn, Cu, and Mn relative to established standards. The ecological risk assessment index revealed that Cd exhibited the most significant level of danger, whereas Cu and As demonstrated a moderate level of danger. The health index values indicate that the levels of As and Zn in adults and children exceeded the acceptable limit, while the levels of Pb, Cr, Fe, Cu, Ni, and Co among children came close to the borderline. The TCR values of Ni for children are beyond the permissible level. PCA revealed that the majority of heavy metals are derived from human activity. Consequently, administration strategies for remediating these open dumps nationwide should include continuous monitoring and surveillance of neutralized dumpsites to avert further contamination.